Tell el-'Ajjul palaces I and II: Context and function - Winter, Holly A. (Palestine exploration quarterly, 2018)
Traditional views on Middle Bronze Age (MBA) palatial function have been challenged by recent work at Tel Kabri, where the excavators have argued against the common identification of southern Levantine palaces as redistributive centres staffed with literate administrators. These innovative ideas surrounding palace function were first developed by Flinders Petrie during excavations at Tell el-'Ajjul in 1931-32. Here he uncovered a series of elaborately constructed elite residences that he identified as 'palaces'. However, when reconsidering Petrie's finds, the results from Ajjul are largely supportive of the Kabri observations. A lack of evidence for key functional attributes of palaces-large-scale storage, administrative paraphernalia and redistributive function - is comparable to that reported at Kabri. A short consideration of similar MBA 'palaces' elsewhere in the southern Levant is supportive of the aforementioned trend, and therefore calls into question the traditionally held views on the function of these elaborate architectural complexes. Either the function generally attributed to these structures is incorrect, or administration and rulership in MBA Canaan leaves no unambiguous residues in the archaeological record.